2005
DOI: 10.4269/ajtmh.2005.72.719
|View full text |Cite
|
Sign up to set email alerts
|

Large Sequence Heterogeneity of the Small Subunit Ribosomal Rna Gene of Plasmodium Ovale in Cambodia

Abstract: Plasmodium ovale malaria has been reported in various countries in southeast Asia, but never in Cambodia. Using a species-specific polymerase chain reaction (PCR) targeting the small subunit (SSU) ribosomal RNA (rRNA) gene, we detected P. ovale in nearly 4% of the inhabitants of a northeastern Cambodian village. Plasmodium ovale was associated with at least one other Plasmodium species, and two quadruple infections were detected. The diagnosis was confirmed by microscopy and by SSU rRNA PCR product sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…LDR-FMA−:LM+ outcomes accounting for 11-20% may have resulted from misdiagnosis, inhibition of PCR amplification of template DNA, or target (ssu rRNA) sequence variability. 48,58 With enhanced capabilities of molecular diagnostic methods to perform semi-quantitative analysis of Plasmodium spe- cies infections, we anticipate that new elements of discordance will be observed, particularly in field studies performed in regions with complex malaria epidemiology. For example, whereas the correlation between LDR-FMA signal strength and the blood smear parasitemia improved with increasing numbers of infected erythrocytes identified by LM (common in concordance studies between microscopists 43,59 ), we observed a wide range of LDR-FMA fluorescence for samples judged to contain a low number of infected erythrocytes by microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…LDR-FMA−:LM+ outcomes accounting for 11-20% may have resulted from misdiagnosis, inhibition of PCR amplification of template DNA, or target (ssu rRNA) sequence variability. 48,58 With enhanced capabilities of molecular diagnostic methods to perform semi-quantitative analysis of Plasmodium spe- cies infections, we anticipate that new elements of discordance will be observed, particularly in field studies performed in regions with complex malaria epidemiology. For example, whereas the correlation between LDR-FMA signal strength and the blood smear parasitemia improved with increasing numbers of infected erythrocytes identified by LM (common in concordance studies between microscopists 43,59 ), we observed a wide range of LDR-FMA fluorescence for samples judged to contain a low number of infected erythrocytes by microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Other PCR-based studies in Southeast Asia report up to 4% of P. ovale malaria in Northeastern Cambodia and 1.03% in Thailand. 16,22,34 The impact of newly emerging pathogens in public health is increasing. Although our data do not confirm the presence of P. knowlesi in Bangladesh, our knowledge of the reservoir, vectors, and ecology of this malaria parasite indicates that Southeastern Bangladesh may be a an environment in which P. knowlesi is likely to be found.…”
Section: Discussionmentioning
confidence: 99%
“…and Papua New Guinea, but using the availability of polymerase chain reaction (PCR)-based techniques for the diagnosis of malaria, this parasite has recently also been reported from a number of countries in South and Southeast Asia. [12][13][14][15][16] So far, infections with P. ovale have not been reported from Bangladesh.…”
mentioning
confidence: 99%
“…One note of caution regarding current PCR-based reports on P. malariae and P. ovale prevalence is that the sequence variation in the SSU rRNA gene target of both species must be considered [68][69][70]. From studies in Southeast Asia, 27% of P. malariae and 36% of P. ovale infections were due to single variant strains in each species that have not been included in all PCR-based diagnostic assays [11].…”
Section: Improved Diagnosis Of P Malariae and P Ovale Infections Bymentioning
confidence: 99%